American Literature in Studia Anglica Posnaniensia 1968-2008 A Comprehensive Bibliography - Semrau, Janusz (Studia Anglica Posnaniensia, 2010)
American Literature in Studia Anglica Posnaniensia 1968-2008 A Comprehensive Bibliography